Cognitive‐behavioural social skills training for first‐episode psychosis: a feasibility study. Issue 5 (29th August 2016) - Herman, Yarissa; Shireen, Huma; Bromley, Sarah; Yiu, Natalie; Granholm, Eric
Abstract: Aim: To conduct a preliminary feasibility examination of cognitive‐behavioural social skills training (CBSST) in a first‐episode psychosis population. Methods: Twenty two first‐episode psychosis clients participated in an 18‐week CBSST group adapted for a younger population. Results: Adaptive functioning significantly improved following group participation and was maintained at 3‐month follow‐up. Conclusion: The CBSST group was feasible and well accepted in the first episode programme. These preliminary findings warrant further testing in a larger trial to determine efficacy.